2006
DOI: 10.1128/mmbr.00025-06
|View full text |Cite
|
Sign up to set email alerts
|

Uses for JNK: the Many and Varied Substrates of the c-Jun N-Terminal Kinases

Abstract: SUMMARY The c-Jun N-terminal kinases (JNKs) are members of a larger group of serine/threonine (Ser/Thr) protein kinases from the mitogen-activated protein kinase family. JNKs were originally identified as stress-activated protein kinases in the livers of cycloheximide-challenged rats. Their subsequent purification, cloning, and naming as JNKs have emphasized their ability to phosphorylate and activate the transcription factor c-Jun. Studies of c-Jun and related transcription factor substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
477
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 521 publications
(502 citation statements)
references
References 365 publications
12
477
0
5
Order By: Relevance
“…Consistently, analysis of JNK activation by immunoblotting in six additional MM cases showed considerable increase of p-JNK in BM plasma cells (selected as CD138 + CD38 hi CD45 low/-) 32 in 5 out of 6 cases compared to normal B cells ( Figure 1B, left). Interestingly, we also observed that intensity of p-JNK2 (p-p54, which is the prominent spliced form of JNK2) was significantly higher than p-JNK1 (p-p46, the prominent spliced form of JNK1) 11 (Figure 1B,right), indicating that JNK2 activity was increased in myeloma plasma cells. Increased levels of p-JNK2 were also found in a panel of MM cell lines compared to p-JNK1 ( Figure 1C).…”
Section: Jnk2 Is Constitutively Active In Myeloma Cellsmentioning
confidence: 76%
See 3 more Smart Citations
“…Consistently, analysis of JNK activation by immunoblotting in six additional MM cases showed considerable increase of p-JNK in BM plasma cells (selected as CD138 + CD38 hi CD45 low/-) 32 in 5 out of 6 cases compared to normal B cells ( Figure 1B, left). Interestingly, we also observed that intensity of p-JNK2 (p-p54, which is the prominent spliced form of JNK2) was significantly higher than p-JNK1 (p-p46, the prominent spliced form of JNK1) 11 (Figure 1B,right), indicating that JNK2 activity was increased in myeloma plasma cells. Increased levels of p-JNK2 were also found in a panel of MM cell lines compared to p-JNK1 ( Figure 1C).…”
Section: Jnk2 Is Constitutively Active In Myeloma Cellsmentioning
confidence: 76%
“…11 As these cellular responses are important in tumorigenesis, JNK signaling has been implicated in human cancers. 11,12 Two major JNK proteins, JNK1 and JNK2, are expressed ubiquitously and each has two different splicing isoforms (p46 and p54).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…JNK phosphorylates a broad spectrum of substrates distributed throughout different subcellular compartments (31). The balance among these site-specific components of JNK signaling determines the biological outcomes (31).…”
Section: Jnk Protein and Basal Jnk Activity In T-all Cells Show Aberrmentioning
confidence: 99%